Anthraquinones derivatives from Heterophyllaea pustulata - Núñez Montoya, Susana Carolina (2006)
From the leaves of Heterophyllaea pustulata two new monomeric anthraquinones, heterophylline (1,6-dihydroxy-7-methoxy-2-methylanthraquinone, 1) and pustuline (2-hydroxy-3-methoxy-7-methylanthraquinone, 2), and one new bianthraquinone, (S)-5,5′-bisoranjidiol [(S)-5,5′-bis(1,6-dihydroxy-2-methylanthraquinone), 3], were isolated. Furthermore, the iridoid glycoside asperuloside and three known flavonoids, quercetin, isoquercitrin, and quercetin-3-O-â-D-glucosyl6′′-acetate, were obtained. The structures were determined by analysis of their spectroscopic data and chemical evidence.